1970
DOI: 10.3329/bmj.v39i3.9952
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Anemia and Iron Folic Acid Supplementation Program in Bangladesh - A Special Article

Abstract: Despite supplementation of iron folic acid tablets over the past few decades, no marked improvement has been noticed in the magnitude of anemia in Bangladesh. It has been a felt need to have a fresh look at the problem of iron/folic acid deficiency anemia prevailing in Bangladesh and the perspective of the supplementation program. Data were collected through a review of a good number of available documents and in-depth interviews of concerned policy makers, stakeholders and care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…Both IFA and calcium supplementation is recommended during pregnancy, particularly in the settings with low intake of iron and calcium and high prevalence of anemia and/or pre-eclampsia. As in many other countries, IFA supplementation in Bangladesh is designed to be delivered through ANC that functions within the context of the government health-care system [ 39 ]. However, there have been obstacles related to the procurement and distribution of IFA supplements, and many PW do not receive or purchase IFA during ANC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both IFA and calcium supplementation is recommended during pregnancy, particularly in the settings with low intake of iron and calcium and high prevalence of anemia and/or pre-eclampsia. As in many other countries, IFA supplementation in Bangladesh is designed to be delivered through ANC that functions within the context of the government health-care system [ 39 ]. However, there have been obstacles related to the procurement and distribution of IFA supplements, and many PW do not receive or purchase IFA during ANC [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 15 % of rural pregnant women take at least 100 tablets and 46 % take none. Access to Fe + folic acid supplementation is scarce, as only 27 % of women make three or more antenatal visits ( 32 ) . Hence, supplemental Fe intake among our study group (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The National Micronutrient Survey 2011–12 estimated an anemia prevalence of 33% among the children of the age group 6–59 months and 26% among the non-pregnant and non-lactating women [14]. Another study reported that childhood anemia decreased with increasing age, with a prevalence of 64% among children of ages 6–23 months and 42% among children of ages 24–59 months [15, 16]. Such high prevalence reported by multiple studies indicates that anemia is a major public health threat in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%